Pengaruh marketing mix multi level marketing terhadap keputusan pembelian produk Oriflame di Pekanbaru - Lasma R.S, Selviana; ', Zulkarnain; ', Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is conducted to analyze the influence of marketing mix multilevel marketing to decision to buy cosmetics products Oriflame in Pekanbaru. The research consists of a dependent variable that is decision to buy (Y) and four independent variables which one dimension of marketing mix consists of product (X1), price (X2), place (X3), promotion (X4). The population in this research is the customer’s of Oriflame with one hundred twenty respondents as the sampleby using purposive sampling technique. Data analysis using quantitative method with SPSSversion seventeen.The result of this research convey that all of the independent variablessimultaneously affect the customer loyalty significantly, and with the partially test proved that promotion gave the biggest impact among the other independent variables. Adjusted R square show at moderate level (sixty point seven percent). It means thirty nine point three percent has affect by other variable beyond this research.The conclusion of this results mean that all the independent variables had a significant value and promotion gave the biggest value of significances to decision to buy cosmetics products Oriflame in Pekanbaru. Therefore, Oriflame Pekanbaru should be more increase the quality of their product from every variables in marketing mix so that costumer could be gives the loyalty to buy.Keywords: Marketing Mix, Multi Level Marketing, Decision to Buy.